Forefronts in research - Sunal, Cynthia S.; Mutua, Kagendo, 1966- (Research on education in Africa, the Caribbean, and the Middle East., 2005)
Research in Education in Africa, The Caribbean, and The Middle East, the Book Series provides a comprehensive view of current and emerging educational knowledge, research, strategies, and policy in these regions. Submissions from all disciplines, as well interdisciplinary perspectives are welcome if manuscripts conform to basic book series goals. The Series goals are: 1). Provide a forum for the dissemination of research on education in the region, 2). Disseminate ideas that enhance both the practical and theoretical aspects of education in the region, 3). Further knowledge and understanding of emerging trends and movements in education in the region and 4). Foster debate about issues such as indigenizing education, women's education, or disability education in the region.